Antibacterial Activities of Soft Coral Extract Lobophytum sp. Towards Pathogenic Bacteria (Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa) - Tanjung, May Juna; Yoswaty, Dessy; Effendi, Irwan (Faculty of Fisheries and Marine, Universitas Riau, 2020)
Soft coral extract of Lobophytum sp. can inhibit the growth of pathogenic bacteria with a weak to very strong category. The purpose of this study was to determine the activity of Lobophytum sp. against pathogenic bacteria Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa and analyze the concentration of Lobophytum sp. effective against pathogenic bacteria E. coli, S. aureus, and P. aeruginosa. Sampling was carried out in the waters of Pigago Island, West Pasaman Regency, West Sumatra. This research method is an experimental method and antibacterial activity test is carried out with agar diffusion diffusion technique. This soft coral extract has the potential to inhibit pathogenic bacteria. The highest inhibitory effect on E. coli bacteria was the highest yield at a concentration of 100% with a yield of 13.95 mm, in the S. aureus bacteria the highest yield at a concentration of 100% with a yield of 12.53 mm and in P.aeruginosa bacteria at a concentration of 100% was 23.87 mm.